4(x+6)-2x-9=9x-6

Simple and best practice solution for 4(x+6)-2x-9=9x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+6)-2x-9=9x-6 equation:



4(x+6)-2x-9=9x-6
We move all terms to the left:
4(x+6)-2x-9-(9x-6)=0
We add all the numbers together, and all the variables
-2x+4(x+6)-(9x-6)-9=0
We multiply parentheses
-2x+4x-(9x-6)+24-9=0
We get rid of parentheses
-2x+4x-9x+6+24-9=0
We add all the numbers together, and all the variables
-7x+21=0
We move all terms containing x to the left, all other terms to the right
-7x=-21
x=-21/-7
x=+3

See similar equations:

| 9x=27-3x | | -3(7m+3)=-156 | | 186=-6(1-4x) | | 9w=21+2w | | -5(1-5b)=-180 | | 5x+-5=50 | | 8(x-2)=4(x-8) | | 3x^2=60^2 | | 92=-2(5n-6) | | -5a12=-18 | | 165=-3(1-8x) | | 4y-2=3y-6+6 | | 960=5(x+18) | | 7(4a+3)=-91 | | 4.2(2x-1.3)=1.7(4+4x) | | 960=5x+18 | | x-3=39-x | | 4(-4-2y)+5y=23 | | 5t^2-24t=28 | | d-29=85 | | 5x/2-x-1/3=9 | | 4+20+2(x-7)=0 | | 10/3=4/x+2 | | 42x^2+41x+9=0 | | 4x+1/2(8x+6)=2(4x)+3 | | 6+0.50x=8+0.25x | | 100+17x=180 | | 3/7-3/4y=1/2-1/2y | | 49/80=x/100 | | 2(2x+11)=8x-14 | | -7p=-3 | | (17+y/y)+(32+y/y)=100 |

Equations solver categories